The existence of geographical clusters of cases of inflammatory polyarthritis in a primary care based register. Issue 2 (1st February 2000) - Silman, Alan; Harrison, Beverley; Barrett, Elizabeth; Symmons, Deborah
Abstract : OBJECTIVES: To determine whether there is any evidence that there are spatial clusters of rheumatoid arthritis in particular, and inflammatory arthritis in general. METHODS: Setting was a population based incidence register of inflammatory arthritis: the Norfolk Arthritis Register (NOAR). All cases identified between 1990–1995 were mapped to place of residence. Statistical evidence of clustering was determined by calculating Poisson probabilities in putative areas. RESULTS: Three clusters were identified including one small area (population 85) where five unrelated cases developed during this time period. There was no obvious greater disease homogeneity within clusters and no common environmental factors were identified. CONCLUSION: Rare clusters of inflammatory polyarthritis do occur. Their significance and cause remain to be elucidated.